2015
DOI: 10.1371/journal.pone.0133854
|View full text |Cite
|
Sign up to set email alerts
|

GPR18 Controls Reconstitution of Mouse Small Intestine Intraepithelial Lymphocytes following Bone Marrow Transplantation

Abstract: Specific G protein coupled receptors (GPRs) regulate the proper positioning, function, and development of immune lineage subsets. Here, we demonstrate that GPR18 regulates the reconstitution of intraepithelial lymphocytes (IELs) of the small intestine following bone marrow transplantation. Through analysis of transcriptional microarray data, we find that GPR18 is highly expressed in IELs, lymphoid progenitors, and mature follicular B cells. To establish the physiological role of this largely uncharacterized GP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 82 publications
(77 reference statements)
1
16
1
Order By: Relevance
“…On the other hand, verbenalin showed inhibitory effects on inflammation responses in GPR18-KO mice, but this effect was significantly weaker than that in WT mice, indicating the role of GPR18 in the antiinflammatory effects or verbenalin. Our results are consistent with a previous study, which showed that GPR18 regulates the reconstitution of mouse small intestine intraepithelial lymphocytes [35]. Other reported functions of GPR18 include its modulation of myocardial function, blood pressure, and intraocular pressure [36,37].…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, verbenalin showed inhibitory effects on inflammation responses in GPR18-KO mice, but this effect was significantly weaker than that in WT mice, indicating the role of GPR18 in the antiinflammatory effects or verbenalin. Our results are consistent with a previous study, which showed that GPR18 regulates the reconstitution of mouse small intestine intraepithelial lymphocytes [35]. Other reported functions of GPR18 include its modulation of myocardial function, blood pressure, and intraocular pressure [36,37].…”
Section: Discussionsupporting
confidence: 93%
“…GPR18 is widely expressed in different tissues and cell types. GPR18 expression was first described in spleen, thymus, bone marrow, leucocytes and macrophages (Gantz et al, 1997;Vassilatis et al, 2003;Kohno et al, 2006;Regard et al, 2008;Takenouchi et al, 2012;Becker et al, 2015). However, receptor is also expressed in the central nervous system (CNS) (Vassilatis et al, 2003;Regard et al, 2008;Penumarti and Abdel-Rahman, 2014), in particular in microglia (Walter et al, 2003), in testis, ovary, lungs, intestine (Gantz et al, 1997;Vassilatis et al, 2003), eye (Caldwell et al, 2013) and cancerous cells (McHugh et al, 2010(McHugh et al, , 2012Qin et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the periphery, regulating the immune system, GPR18 is involved in resolving inflammation (Burstein et al, 2011), regulating macrophage apoptosis (Takenouchi et al, 2012) and controlling the fate of intestine intraepithelial lymphocytes following bone marrow transplantation (Becker et al, 2015). It is also involved in regulating hemodynamic responses (Parmar and Ho, 2010;Penumarti and Abdel-Rahman, 2014;Al Suleimani and Al Mahruqi, 2017;Matouk et al, 2017), cell migration (Walter et al, 2003;McHugh et al, 2010) and intraocular pressure (Miller et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Of importance, the latest study by Becker et al. confirms that GPR18 controls reconstitution of mouse small intestine intraepithelial lymphocytes following bone marrow transplantation and suggests that manipulation of GPR18 signals could be used to modulate inflammatory disorders . Therefore, it is possible to suggest that GPR18 may play an important immunoregulatory role in the pathophysiology of inflammation associated with obesity and related metabolic disorders (Fig.…”
Section: Gpr18: Potential Role In Obesity and T2d?mentioning
confidence: 99%